Evaluasi Kondisi Ekosistem Lamun Thalassia hemprichii Melalui Transplantasi Metode Peat Pot Substrate Modification di Perairan Pantai Desa Suli Kabupaten Maluku Tengah - Rosmawati, Rosmawati; Assagaf, Gamar (Biosel Biology Science and Education, 2025)
Thalassia hemprichii is a type of seagrass that grows in the coastal waters of Suli Village, Central Maluku Regency and its distribution is quite wide, but its population is starting to decrease considering the damage to the seagrass, including due to the influence of waves and currents which cause the seagrass to be detached from its substrate or damage originating from the activities of the surrounding community such as coastal reclamation, waste pollution and "bameti" activities. Seagrass transplantation is one way to repair damaged seagrass beds. This study aims to analyze the survival rate, growth rate, biomass and physical and chemical factors of the waters that affect the growth of T. hemprichii seagrass. If so far the peat pot seagrass transplantation method uses polybags containing substrate from the donor area, this study tries to use substrate from the transplant area. The results showed that T. hemprichii had a survival rate of 100%. The average leaf growth rate in the 1st observation period was 0.145 cm/day, while in the 2nd observation period it was 0.172 cm/day. Seagrass leaf biomass ranges from 0.002 gbk/m2 –0.014 gbk/m2 with a total biomass value of 0.270 gbk/m2. Decree of the Minister of Environment Number 51 of 2004 concerning Sea Water Quality Standards, the value of the physical and chemical parameters of waters is still within the range of environmental parameters of marine waters that support the growth of T. hemprichii.  Keywords: Transplantation, Peat Pot, Substrate, Modification Method